Urgensi Pendidikan Seks melalui Pendidikan Karakter bagi Anak Usia SD - Muhimmah, Syiddatul; Fajrin, Nilamsari Damayanti (Universitas Terbuka, 2022)
Sex education is very important for elementary school age students if it is implemented properly, but there are still many teachers and parents who are still unable to implement it. Characteristics of students who tend to be stubborn and difficult to advise will find it difficult to absorb important knowledge given by teachers and parents. If students lack knowledge about sex education, it is possible that sexual violence can occur. Sexual violence against children can occur if the child does not know at all about sex education. This study aims to describe the problems found regarding the urgency of sex education through character education at the age of elementary school children. This article uses a qualitative method with a case study approach model. Research that uses the case study method, carried out an in-depth examination of a case by using systematic methods of observing, collecting data, analyzing information, and reporting the results. The results of the study can be concluded that sex education can be applied in learning at school by providing knowledge about the function of the reproductive organs by instilling moral, ethical, and religious commitments, so as to avoid abuse of reproductive organs. If the child already understands about sex education, then it can be ascertained that the child can be protected from sexual violence.